Ethyl caffeate ameliorated amyloid‐beta42 protein‐associated toxicity in PC12 cells and Drosophila melanogaster. Issue 12 (26th October 2021) - Tan, Florence Hui Ping; Hadri, Nurulhuda Athirah Binti; Najimudin, Nazalan; Watanabe, Nobumoto; Azzam, Ghows
Abstract : Aim: Alzheimer's disease (AD) is the most pervasive neurodegenerative disorder in societies globally. Till now, the mechanism behind this disease is still equivocal. Amyloid‐beta42 protein (Aβ42), the most toxic and aggressive Aβ species, is the main focus of this study. The naturally occurring ethyl caffeate (EC) is associated with various medicinal properties. Here, EC was tested for its protective properties against Aβ42's toxic effects. Methods: As treatment of Aβ42 has been shown to cause neuronal cell death, EC was first screened with Aβ42‐incubated PC12 neuronal cells. Next, the compound was tested on the Drosophila melanogaster AD model using the rough eye phenotype assay, lifespan assay and negative geotaxis assay. Results: EC ameliorated PC12 cells from cell death linked to Aβ42 exposure. Using Drosophila expressing human Aβ42, feeding of EC was able to partially rescue the rough eye phenotype, lengthen the lifespan of AD Drosophila and enhanced the mobility of middle‐aged AD Drosophila . Conclusion: Overall, the results of this study showed that EC might possess therapeutic properties for AD. Geriatr Gerontol Int 2021; 21: 1125–1130 .